Antihyperglycemic Effect of Aqueous Leaf Extract of Mimusops elengi against Streptozotocin-Induced Diabetic Male Albino Rat: Antihyperglycemic Effect of Aqueous Leaf Extract of Mimusops elengi against Streptozotocin-Induced Diabetic Male Albino Rat - Narendiran, Dr. N. Jothi (International Journal of Pharmaceutical & Biological Archive, 2018)
Objective: The present study was hypothesized to evaluate the antihyperglycemic effect of aqueous leaf extract of Mimusops elengi on streptozotocin (STZ)-induced diabetic animals. Materials and Methods: Antidiabetic activity of M. elengi leaf extract at a dosage of 250 mg/kg body weight was evaluated. Results: The activity levels of glucose, triglycerides, total cholesterol, and serum glutamic pyruvic transaminase were significantly elevated in STZ-induced diabetic animals when compared to that of normal animals. After supplemented with aqueous leaf extract of M. elengi, animals group recorded significant lower blood glucose level. Conclusion: The aqueous leaf extract of M. elengi has been potent antidiabetic effect in male albino rat.